Interlinking OF IoT, Big data, Smart Mobile app with Smart Garbage Monitoring - Gorli, Ravi (International Journal of Computer Sciences and Engineering, 2025)
Interlinking of IOT, Big Data and Android, Now arises a question, what’s link between these technologies? As, IoT is a technology where world is stepping towards future development, Internet of Things (IoT). Internet is interconnecting of networks, Things means Devices or Objects (Interaction between Objects). IoT is not mainly creating smart gadgets or connecting more things to the internet, machine-to-machine (M2M) technologies can be seen as the first phase, in the next phase the connectivity of physical objects together connected in support of intelligent decision making operated with Sensors and Actuators. A Sensor is used for grasping the input from any object and an Actuator is used for activating the device based on the input taken from a Sensor, here comes the need of Big data Analytics, Data was getting seriously big even before IoT entered the picture. If Big data is “Heart” of advancement, IoT is the “Soul”. Where sensors sense objects continuously time to time and forward in every bit of second, processing which in cause memory load that should be maintained, so the huge amounts of data should be collected and maintained with Big data. Data Analytics for extracting actual information from huge amounts of data. Now comes Smart App which has more scope with introducing of smart gadgets where maximum people are aware the applications in them. So for user interaction purpose we introduce mobile apps by directly giving access to the users. In this paper I have given brief introduction of Interlinking of IoT, Big Data and Smart mobiles focusing on one of major problem in society i.e., Garbage Monitoring replacing with Smart Garbage Monitoring.